2018
DOI: 10.1371/journal.pone.0203429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient information needs in type 2 diabetes: A cross sectional study of questions

Abstract: This study set out to analyze questions about type 2 diabetes mellitus (T2DM) from patients and the public. The aim was to better understand people’s information needs by starting with what they do not know, discovered through their own questions, rather than starting with what we know about T2DM and subsequently finding ways to communicate that information to people affected by or at risk of the disease. One hundred and sixty-four questions were collected from 120 patients attending outpatient diabetes clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…More than 57% of the participants stated that they had a need for information on each diabetes-related topic [10]. It has been suggested that information needs may change over the course of the disease [6,19,29,30]. It is therefore conceivable that individuals with a recent diagnosis represent a subgroup with specific (higher) information needs.…”
Section: Discussion Of the Findings And Comparison To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 57% of the participants stated that they had a need for information on each diabetes-related topic [10]. It has been suggested that information needs may change over the course of the disease [6,19,29,30]. It is therefore conceivable that individuals with a recent diagnosis represent a subgroup with specific (higher) information needs.…”
Section: Discussion Of the Findings And Comparison To Other Studiesmentioning
confidence: 99%
“…We identified a second class encompassing individuals with 'high needs' for information on all diabetes-related topics with no thematic focus. Crangle and colleagues (2018) reported a change in the need for information upon the onset of complications, noting that 'with the onset of complications, a person may be energized by the complications to manage his/her diabetes' [30]. Ormandy (2011) also reported that the perception of disease-related symptoms drives the recognition and verbalization of information needs [7].…”
Section: Discussion Of the Findings And Comparison To Other Studiesmentioning
confidence: 99%
“…In Jordan, the descriptive correlational study (n = 1002) found that perception about T2DM treatment was worse among women than men, and heart disease as a comorbidity with diabetes was also a significant indicator for low treatment satisfaction 47 . The researchers identified the phases of T2DM progression: Prior to any Diagnosis, Pre -diabetic (diagnosed), Onset of T2DM, Health Maintenance and Prevention, Complications-Minor or Major 48 . In Europe initiated the DE -PLAN project (Diabetes in Europe: Prevention Using Lifestyle, Physical Activity and Nutritional Intervention) and its implemented by the principles of lifestyle intervention 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus may increase the risk of heart failure in both men and women in all age groups, especially in young people 6 . In Lithuania, the results of the research (n = 606) stated that 98% of patients with coronary heart disease had at least one of four conventional risk factors: hypertension (47.7%), diabetes (12.9%), dyslipidemia (90.1%), smoking (24.1%) 7 . In order to reduce the epidemic of coronary heart disease, much greater emphasis should be given to identify and to improve prevention of conventional risk factors as well as the lifestyle of the patient 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of diabetes quadrupled between 1980 and 2014, affecting 432 million globally, 90% of whom suffer from type 2 diabetes . When surveyed, type 2 diabetic patients are most interested in being informed about complications and optimal treatment management . People with diabetes have a 2‐ to 4‐fold higher risk of mortality from cardiovascular disease .…”
mentioning
confidence: 99%